MMCL Order Manage System For Masak-Masak Cik Liza - Kamalrudzaman, Nur Husna Nabihah; Sulaiman, Rabatul Aduni (Applied Information Technology And Computer Science, 2024)
These days, an increasing number of individuals, especially those with busy work schedules are choosing the convenience of ordering their meals online. Masak-Masak Cik Liza (MMCL) is a small food home-based online business that manages its operations and order data manually. This practice often results in errors and oversights in handling the business data. The main objective of this project is to develop a comprehensive solution that effectively organizes MMCL's business data and streamlines its management processes. To ensure that the system serves its intended purpose, the requirements of the users involved in the business process are gathered. By implementing a computerized management system, MMCL can significantly enhance its business efficiency by automating key processes, ranging from order recording to order preparation and fulfillment.